Validation and Psychometric Properties of the Brazilian Version of the Subjective Happiness Scale - Damásio, Bruno Figueiredo; Federal University of Rio Grande do Sul (UFRGS) (2013)
This paper aimed to adapt the Subjective Happiness Scale to Brazil and gather evidences of construct validity to the scale. Participants were 600 subjects (50% men), aged from 18 to 70 years old (M = 30.1; SD = 10.6). Sample was split to cross-validate the results. Exploratory factor analysis (n1 = 300) achieved a reliable single-factor solution, with all items loading satisfactorily on the factor. Confirmatory factor analysis (n2 = 300) corroborated the singlefactor solution with excellent goodness-of-fit indexes. Evidences of convergent validity are also provided with three related constructs: self-esteem, life satisfaction and hope. The adapted scale showed strong evidences of validity and seems appropriate to evaluate subjective happiness on Brazilian adults.